The Role of Academic Staff in Confronting Extremist Ideology - Al-Lahebi, Prof. Dr. Qahtan Mahboub Fadhil Al-Lahebi; Abdul-Razzaq, Assoc. Prof. Dr. Mahj Ghanem Abdul-Razzaq (Sulaimani Journal for Humanities, 2026)
This study sheds light on extremist ideology—its causes, manifestations, and dangers—and its spread among students and youth. It particularly emphasizes the role of academic staff in fulfilling their critical mission of preserving religion, the nation, and future generations. The term "academic staff" in this study refers to degree holders and qualified professionals, who represent the conscious and enlightened segment of society, and serve as positive role models. Their influence in countering extremist thought is enacted through general and specialized awareness lectures, as well as via visual, auditory, and print media. Moreover, their contribution is reflected through their participation in conferences, seminars, and workshops aimed at promoting moderation, critical thinking, and civic responsibility.
Keywords: Extremist Ideology; Academic Staff; Youth; Awareness; Education; Radicalization Prevention